The potential of Asystasia intrusa weed of Acanthaceae family as a cover crop in oil palm plantations - Halus Satriawan; ZAHRUL FUADY; ERNAWITA ERNAWITA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Satriawan H, Fuady Z, Ernawita. 2020. The potential of Asystasia intrusa weed as a cover crop in oil palm plantations. Biodiversitas 21: 5711-5718. Weeds generally found in oil palm plantations, one of which is dominant is Asystasia intrusa. This weed has begun to be used as a cover crop on oil palm land because it is assumed to have a beneficial effect. The purpose of this research is to explore the potential of Asystasia intrusa in growing as a cover crop on oil palm plantations. The experimental arrangement used was split-plot design. Oil palm plan’s ages were used as the main plot, while the spacing plant (Asystasia intrusa) as the subplots. Experiments were done in triplicate. The results showed that Asystasia intrusa has the potential to be used as a cover crop in oil palm plantations, since it meets several requirements, such as quickly covering the land (12 WAP), fast decomposing (30-60 days), tolerance to shade. This was indicated by the growth percentage of 97.56%, containing nutrients N (1.65-1.77%), P (0.29%), and K (4.6-4.97%), as biomass (0.9 t C/ha/year) and soil carbon stocks (39.52-41.16 t/ha/year). The studied weed also has the ability to increase soil carbon stock up to 119%.